Experience and outcomes for PAs in a neonatal circumcision clinic. Issue 10 (October 2020) - Colón-Sanchez, Kaity; Middleton, Tiernan; Ellsworth, Pamela
ABSTRACT: Objective: To evaluate the outcomes of neonatal circumcision performed by a PA in pediatric urology. Methods: A retrospective review was performed of infants evaluated for neonatal circumcision by a single PA in pediatric urology over 30 months. Technique, age and weight at circumcision, presence or absence of genital anomalies, and complications were gathered. Results: Of the 371 male infants evaluated for neonatal circumcision, 276 underwent the procedure. Complications included retained Plastibell (2.1%), penile adhesions (1.1%), swelling (1.8%), and cosmetic concerns (0.73%). Eighteen unanticipated postprocedure visits occurred—four in the ED and 14 in the outpatient clinic. No acute procedural complications occurred. One patient (0.3%) underwent lysis of penile adhesions at age 19 months. Conclusion: Neonatal circumcisions are commonly performed by nonsurgeons with variable formal circumcision training. These data support that well-trained PAs can perform neonatal circumcisions with low complication rates.